Spatiotemporal approach for estimating potential CO2 sequestration by reforestation in the Korean Peninsula - Lee, Sle-gee; Kim, Hyun-Jun (Frontiers in Forests and Global Change, 2023)
A forest is one of the carbon sinks in the terrestrial ecosystem; it is a major target for securing CO2 sequestration to achieve carbon neutrality. Reforestation is a forest management method that could attain carbon fixation and forest degradation recovery at the same time, but quantitative research has not been actively conducted. The purpose of this study is to identify the target areas for reforestation through changes in land cover in the Korean Peninsula and to quantify the potential CO2 sequestration effect of reforestation. According to the land cover change through satellite imagery, the area of settlements in the Republic of Korea (ROK) was the most dominant (+3,371 km2), and the main change occurred from cropland to settlements. The forest area increased by +1,544 km2 from 68,264 km2 in the 1980s to 69,809 km2 in the late 2010s. The forest decreased by 7,526 km2, accounting for 5.68% of the entire land area of the Democratic People's Republic of Korea (DPRK), and cropland increased by 5,222 km2 which is 5.12%. Assuming that the target of reforestation is an area whose land cover was a forest in the past and then converted to cropland, wetland, or bare ground, the area of the target decreased as the reference period was applied more recently. As a result of comparing the late 2000s to the late 2010s, the ROK's annual net carbon sequestration due to reforestation is predicted to be 10,833,600 Mg CO2 yr−1 in 2050 and 20,919,200 Mg CO2 yr−1 in 2070. In the DPRK, 14,236,800 Mg CO2 yr−1 in 2050 and 27,490,400 Mg CO2 yr−1 in 2070 were predicted. Reforestation in the Korean Peninsula was analyzed to have sufficient potential to secure a carbon sink, and the DPRK in particular was analyzed to be able to play a role in overseas reforestation.